Titik Singgung Hukum Islam dengan Hukum Adat pada Naskah Perundang-Undangan Kerajaan Islam di Nusantara - Anis Masykhur (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2020)
The study of the intersection of Islamic law with customary law in the legislation texts of the Islamic kingdoms in the Indonesian Archipelago is intended to describe the flexibility of Islamic law when it meets customary law, and vice versa. This research is a comparative study between the laws that were made into the sultanate law in the archipelago in the 16-18 century AD. The nature of Islamic law is believed to have the ability to adapt (legal adaptability) with other laws. One theory that can strengthen this statement is the existence of one of the five major principles in the science of Usul al-Fiqh, namely